Assessment Of Policies, Determinants And Characteristics Of Generic Medicines Entry Into The Malaysian Pharmaceutical Market - Fatokun, Omotayo Oladuntoye (2014)
The Malaysia healthcare system relies on the availability of generic equivalents of innovator medicines to curtail the rising pharmaceutical expenditure. This study assesses the dimensions and dynamics of generic medicines entry following patent expiration on the innovator drug products in Malaysia. This was a mixed-methods study. The findings of this research revealed 14 categories of policies and regulatory measures with varying effects on generic entry in Malaysia. The mail survey yielded a usable response rate of 53.8% (14/26) following four successive mailings. Reliability coefficients for the multi-item entry decisions and entry barriers variables were 0.62 and 0.82 respectively. The major factors driving generic development and entry decisions in Malaysia were pre-patent expiration market value of innovator’s products (Meanrank= 3.75, M=4.14, SD=1.03), cost of generic development and approval (Mean-rank= 3.04, M=3.50, SD=1.40) and compatibility of the new generic medicine with firms’ existing products range (Mean-rank=2.79, M=3.64, SD=1.2). The innovator product’s pre-patent expiration market value was a significant entry driver for domestic-market oriented generic firms as compared with export-market oriented firms (U=0.00, Z=- 2.36, p=0.01). The Major barriers to generic medicines development and market entry in Malaysia were patent clustering by innovator firms (Mean-rank=7.96, M=4.07, SD=0.83) and earlier market entry of imported generics (Mean-rank=7.75, M=4.07, SD=0.73).